Analisis Hubungan Variabel-Variebel Penting pada Usaha Kecil Kerajinan Rambut di Desa Karangbanjar Kabupaten Purbalingga - Agus Arifin (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2008)
Small enterprises have proved their important role to economic condition in a country. Based on financial side, small enterprises could answer quickly and flexibility to economic crisis shocks rather than medium and large enterprises. Based on employee absorption, small enterprises could pass the crisis without reducing the number of employee. Thus, small enterprises are to be anchor for societies and local governments in order to economic improvement and social welfare, even in recent decentralization era. Local government tries to develop potential endowments through empowering the advantage and potential sectors and products. This research aim is to study important variables and analyze relationship between them in small enterprise of hair production in Karangbanjar village, Purbalingga regency. The tools used in this research are Spearman-rank Correlation to know strong correlation between variables and Ordinary Least Square (multiple regression) to analyze functional relationship between them. In this research, small enterprises were separated between cottage and small industries.The results obtained from this research are based on correlational analysis, there is strong correlation between variables studied, such material, wage expenditure, capital, asset, and product value. Functional relationship analysis shows that in cottage industry, material affects product value significantly while in small industry, that is wage expenditure. These results are suitable with the hypothesis in this research. Keywords: hair production, production, small industry, cottage industry